Answer:
164.848 m
Step-by-step explanation:
Answer:
2/3
Step-by-step explanation:
Answer:
No solution
Step-by-step explanation:
Actually, you have only one equation here. We will solve it for x.
Performing the indicated multiplication, we obtain:
10-2(2x+1)=4(x-2) => 10 - 4x - 2 = 4x - 8, or 10 - 2 = -8. This can never be true, so this equation has no solution.
ANSWER
![{(m + 2)}( {n}^{2} + 2n + m + 1)](https://tex.z-dn.net/?f=%7B%28m%20%2B%202%29%7D%28%20%7Bn%7D%5E%7B2%7D%20%2B%202n%20%2B%20m%20%2B%201%29)
EXPLANATION
The given expression is
![{(m + 2)}^{2} - (m + 2) + mn(n + 2) + 2n(n + 2)](https://tex.z-dn.net/?f=%20%7B%28m%20%2B%202%29%7D%5E%7B2%7D%20-%20%28m%20%2B%202%29%20%2B%20mn%28n%20%2B%202%29%20%2B%202n%28n%20%2B%202%29)
We factor to get,
![= {(m + 2)}(m + 2 - 1) +n (n + 2) (m+ 2)](https://tex.z-dn.net/?f=%20%3D%20%7B%28m%20%2B%202%29%7D%28m%20%2B%202%20-%201%29%20%2Bn%20%28n%20%2B%202%29%20%28m%2B%202%29)
This implies that,
![= {(m + 2)}(m + 1) +n (n + 2) (m+ 2)](https://tex.z-dn.net/?f=%20%3D%20%7B%28m%20%2B%202%29%7D%28m%20%2B%201%29%20%2Bn%20%28n%20%2B%202%29%20%28m%2B%202%29)
We factor further to obtain,
![= {(m + 2)}((m + 1) +n (n + 2))](https://tex.z-dn.net/?f=%20%3D%20%7B%28m%20%2B%202%29%7D%28%28m%20%2B%201%29%20%2Bn%20%28n%20%2B%202%29%29)
or
Grace’s because she followed the order of operations. Addition and subtraction first, then multiply and divide.